Bioinformatics analysis combined with untargeted metabolomics reveals lipid metabolism-related genes and their biological markers in chronic spontaneous urticaria - Hu, Zhiming; Wang, Qiong; Wang, Yuqi; Gao, Yao; Hao, Jianhua; Li, Rui; Zhao, Hua; Guo, Shuping; Cui, Hongzhou (Frontiers in Genetics, 2025)
BackgroundChronic spontaneous urticaria (CSU) is an immune-driven skin condition with a multifaceted and not yet fully understood pathogenesis. Although substantial research has been conducted, viable therapeutic targets are still scarce. Studies indicate that disruptions in lipid metabolism significantly influence the development of immune-related disorders. Nevertheless, the precise relationship between lipid metabolism and CSU remains underexplored, warranting further investigation.MethodsWe obtained the GSE72540 and GSE57178 datasets from the Gene Expression Omnibus (GEO) repository. For the GSE72540 dataset, we identified differentially expressed genes (DEGs) and performed weighted gene co-expression network analysis (WGCNA) on them. The identified DEGs were cross-referenced with lipid metabolism-related genes (LMRGs). To identify hub genes, we constructed a protein-protein interaction (PPI) network. These hub genes were validated using the GSE57178 dataset to identify potential diagnostic markers. Additionally, gene set enrichment analysis (GSEA) and receiver operating characteristic (ROC) curve analysis were employed to evaluate their diagnostic potential. In the CSU mouse model, we further validated the expression levels of these hub genes. Finally, untargeted metabolomics was conducted to detect lipid metabolism-related metabolites in the serum of CSU patients.ResultUsing bioinformatics analysis, three hub genes were identified: SLC2A4, PTGS2, and PLA2G2A. In skin tissues from CSU-like mouse models, the mRNA levels of PTGS2 and PLA2G2A were significantly upregulated compared to the control group. Additionally, untargeted metabolomics revealed 60 distinct lipid metabolites, with a marked increase in arachidonic acid levels observed in the CSU group.ConclusionPTGS2 and PLA2G2A are key hub genes for CSU, and arachidonic acid can serve as a potential serum biomarker.